Surgical Telementoring Without Encumbrance: A Comparative Study of See-through Augmented Reality-based Approaches. Issue 2 (August 2019) - Rojas-Muñoz, Edgar; Cabrera, Maria Eugenia; Andersen, Daniel; Popescu, Voicu; Marley, Sherri; Mullis, Brian; Zarzaur, Ben; Wachs, Juan
Abstract : Objective: This study investigates the benefits of a surgical telementoring system based on an augmented reality head-mounted display (ARHMD) that overlays surgical instructions directly onto the surgeon's view of the operating field, without workspace obstruction. Summary Background Data: In conventional telestrator-based telementoring, the surgeon views annotations of the surgical field by shifting focus to a nearby monitor, which substantially increases cognitive load. As an alternative, tablets have been used between the surgeon and the patient to display instructions; however, tablets impose additional obstructions of surgeon's motions. Methods: Twenty medical students performed anatomical marking (Task1) and abdominal incision (Task2) on a patient simulator, in 1 of 2 telementoring conditions: ARHMD and telestrator. The dependent variables were placement error, number of focus shifts, and completion time. Furthermore, workspace efficiency was quantified as the number and duration of potential surgeon-tablet collisions avoided by the ARHMD. Results: The ARHMD condition yielded smaller placement errors (Task1: 45%, P < 0.001; Task2: 14%, P = 0.01), fewer focus shifts (Task1: 93%, P < 0.001; Task2: 88%, P = 0.0039), and longer completion times (Task1: 31%, P < 0.001; Task2: 24%, P = 0.013). Furthermore, the ARHMD avoided potential tablet collisions (4.8 for 3.2 seconds in Task1; 3.8 for 1.3 seconds in Task2). Conclusion: The ARHMD system promises to improve accuracy and to eliminate focus shifts in surgical telementoring. Because ARHMD participants were able to refine their execution of instructions, task completion time increased. Unlike a tablet system, the ARHMD does not require modifying natural motions to avoid collisions.